PENGARUH EMPLOYEE ENGAGEMENT DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM MITRA ABADI - Indah Dela Wijayanti; Rauly Sijabat (Fakultas Ekonomi dan Bisnis Universitas PGRI Semarang, 2022)
This study aims to know the influence of employee engagement and job satisfaction on employee performance both partially and simultaneously in telecommunications companies. The method used in this study is quantitative method and uses data analysis techniques, namely descriptive analysis and path analysis. Data collection in this study is by disseminating questionnaires with a six-point likert scale and the number of research statements as many as 52 statements distributed to 227 employees of telecommunications companies in the West Java region. The results showed that employee engagement and job satisfaction have a significant positive influence on employee performance. With a coefficient of determination (R2) of 0.364 or 36.4% showed that employee engagement and job satisfaction were shown to have an influence of 36.4% on employee performance. So that companies that have employees with a good sense of engagement to the company and the needs of employees are met to provide satisfaction for employees, it will be obtained employees who have a high loyalty value and dedicate their time to help the company in achieving its goals.